2016
DOI: 10.1186/s12888-016-0780-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical correlates of vitamin D deficiency in established psychosis

Abstract: BackgroundSuboptimal vitamin D levels have been identified in populations with psychotic disorders.We sought to explore the relationship between vitamin D deficiency, clinical characteristics and cardiovascular disease risk factors among people with established psychosis.MethodsVitamin D levels were measured in 324 community dwelling individuals in England with established psychotic disorders, along with measures of mental health, cardiovascular risk and lifestyle choices. Vitamin D deficiency was defined as s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
66
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(68 citation statements)
references
References 47 publications
2
66
0
Order By: Relevance
“…Hypertension was only measured in two included studies, with one finding a significant negative correlation with vitamin D (Lally et al, 2016) and the other finding no significant effects (McCue et al, 2012). Finally, only one included study examined waist circumference finding a significant negative correlation with vitamin D (Lally et al, 2016).…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Hypertension was only measured in two included studies, with one finding a significant negative correlation with vitamin D (Lally et al, 2016) and the other finding no significant effects (McCue et al, 2012). Finally, only one included study examined waist circumference finding a significant negative correlation with vitamin D (Lally et al, 2016).…”
Section: Discussionmentioning
confidence: 97%
“…However, there is evidence to suggest that vitamin D among people with psychosis is correlated with the season of blood sampling (Belzeaux et al, 2015;Berg et al, 2010;Crews et al, 2013;Grønli et al, 2014;Lally et al, 2016;Zhu et al, 2015) and parathyroid hormone levels (Bergemann et al, 2008;Rey-Sánchez et al, 2009;Schneider et al, 2000), the latter being negatively correlated to vitamin D. What this review highlights are a multitude of variables that have been found to not significantly correlate with vitamin D within the patient population including but not limited to: BMI, age, gender, smoking, duration of illness and GAF score.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations